Elucidating the potential of Annona muricata L. grown in Sri Lanka to be used in developing an anticancer drug against colorectal and breast cancers - Onela Canith Pathirana; Madhavi Priyanka Paranagama; Kavindra Kumara Wijesundera; Thilini Anupama Nanayakkarawasam Mahakapuge; Abeykoon Mudiyanselage Anuththara Upamali Abeykoon; Jayantha Rajapakse (BMC, 2024)
Abstract Background Since ancient times many traditional medicine systems around the world have been using different parts of Annona muricata L. (AM), to treat cancer. Indeed, numerous in vitro and in vivo studies also have shown anticancer properties of different solvent extracts of different parts of AM. Even the same part of the plant has shown different levels of anticancer properties based on geographical variations. Therefore, in the present study, the anticancer potential of the leaves, fruit pulp and the fruit peel of the AM that is grown in Sri Lanka was comparatively analyzed with the intention of identifying the most suitable part to be developed into a nutraceutical with anticancer effects. Methods Freeze-dried aqueous extracts of immature leaves (ILAM), mature leaves (MLAM), pulp (PAM) and peel (PLAM) of AM were analyzed for their antioxidant activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging and 2,2-azinobis-3-ethylbenzothiozoline-6-sulfonic acid (ABTS) cation decolorization assays. Their cytotoxicity on breast cancer (MCF-7) cells, colorectal adenocarcinoma (DLD-1) cells and normal human gingival fibroblasts (HGF-1) were determined by the 3-(4,5- dimethylthiazole-2-yl)-2,5-diphenyl-tetrazoliumbromide (MTT) assay. Their effect on mRNA expression of proapoptotic (Bax and caspase-7) and cell cycle arresting (p21) genes was analyzed by RT- qPCR in the same cell lines. Results ILAM demonstrated the highest antioxidant activity in both DPPH and ABTS assays followed by MLAM, PLAM and PAM. In the MTT assay, both ILAM and MLAM demonstrated strong cytotoxic activity against MCF-7 and DLD-1 cell lines while there were no cytotoxic effects on the normal human cell line HGF-1. Both ILAM and MLAM demonstrated concentration-dependent upregulation of mRNA expression of cell cycle arresting gene p21 and apoptosis inducing genes Bax and caspase-7 in MCF-7 and DLD-1 cells. Conclusion The AEAM leaves grown in Sri Lanka has significantly higher antioxidant activity as well as selective cytotoxic effects on MCF-7 and DLD-1 cancer cells compared to its PL and P counterparts. Further, the AEAM leaves induced mRNA expression of the anticancer genes p21, Bax and caspase-7, indicating its potential to be developed into an anticancer drug against breast and colorectal cancer.